Language in the Buddhist tantra of Japan: Indic roots of mantra - Payne, Richard K. (Bloomsbury Academic, 2018)
"Language in the Buddhist Tantra of Japan dismantles the preconception that Buddhism is a religion of mystical silence, arguing that language is in fact central to the Buddhist tradition. By examining the use of "extraordinary language" - evocations calling on the power of the Buddha - in Japanese Buddhist Tantra, Richard K. Payne shows that such language was not simply cultural baggage carried by Buddhist practitioners from South to East Asia. Rather, such language was a key element in the propagation of new forms of belief and practice. In contrast to Western approaches to the philosophy of language, which are grounded in viewing language as a form of communication, this book argues that it is the Indian and East Asian philosophies of language that shed light on the use of language in meditative and ritual practices in Japan. It also illuminates why language was conceived as an effective means of progress on the path from delusion to "awakening"."--Bloomsbury Publishing